The influence of different air flows introduced on the thermal comfort of car passengers during the cooling period – Numerical Study. Issue 1 (May 2021) - Danca, P A; Nastase, I; Bode, F
Abstract: In this article the effects of different airflow rates introduced by the ventilation system are investigating by numerical simulation over the thermal comfort of the driver in a regular vehicle. The 3D LDV (Laser Doppler Velocimetry) measurement for the diffusers velocity field was imposed as boundary condition at the inlets of the investigated domain. Also, the flow rate discharged by each diffuser was measured for the first three positions of the air conditioning system. In the numerical model which was previously validated we imposed the boundary conditions from the experimental sessions. Thermal comfort was assessed by calculation of the equivalent temperature on the surface of a virtual manikin on the driver place and by the determination of the maps of Predicted Mean Vote (PMV) and the Draft rate indices. A first conclusion is that the results of the three flowrates may assure the comfort of the front passengers and a draft sensations and uncomfortable state for the rear passengers.